Detection of antibodies against bovine viral diarrhoea virus in goats of four provinces of Lima, Peru - Benito F., Diana (2018)
The aim of this study was to determine antibodies against the bovine viral diarrhea virus (BVDv) in serum samples of adult goats, females and males, of intensive, semi-extensive and transhumant production systems, from 89 farmers of four provinces of the department of Lima: Huaura (n=196), Huaral (n=233), Canta (n=153) and Lima (n=172). The detection of neutralizing antibodies against the BVDv in serum samples (n=754) was done by the viral neutralization test. The results showed that 1.2% (9/754) of the samples had antibodies against the virus. Seroreactive samples were from transhumant goats from the provinces of Canta and Huaura.